8(m-n)-3(2m+3)=

Simple and best practice solution for 8(m-n)-3(2m+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(m-n)-3(2m+3)= equation:


Simplifying
8(m + -1n) + -3(2m + 3) = 0
(m * 8 + -1n * 8) + -3(2m + 3) = 0
(8m + -8n) + -3(2m + 3) = 0

Reorder the terms:
8m + -8n + -3(3 + 2m) = 0
8m + -8n + (3 * -3 + 2m * -3) = 0
8m + -8n + (-9 + -6m) = 0

Reorder the terms:
-9 + 8m + -6m + -8n = 0

Combine like terms: 8m + -6m = 2m
-9 + 2m + -8n = 0

Solving
-9 + 2m + -8n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 2m + 9 + -8n = 0 + 9

Reorder the terms:
-9 + 9 + 2m + -8n = 0 + 9

Combine like terms: -9 + 9 = 0
0 + 2m + -8n = 0 + 9
2m + -8n = 0 + 9

Combine like terms: 0 + 9 = 9
2m + -8n = 9

Add '8n' to each side of the equation.
2m + -8n + 8n = 9 + 8n

Combine like terms: -8n + 8n = 0
2m + 0 = 9 + 8n
2m = 9 + 8n

Divide each side by '2'.
m = 4.5 + 4n

Simplifying
m = 4.5 + 4n

See similar equations:

| -2x+8=2x+5 | | 1+2(-2+2s)=-3+4s | | 7h-12=3h-5 | | -2(n+4)-4n= | | 1+2t=-3+4s | | 6x+2=78 | | -10=t-3 | | 23=-10(z-92)+73 | | -2k^5+8k^4= | | 8=2(6)-4 | | 8(x+y)+2x+3= | | 2(4z+2)-8=60 | | 3+6h=2h+14 | | X/5-8=3 | | (x-5)/10=10/3 | | 6x+10=31 | | (y+12)+(y-18)=180 | | 15.4+d=23 | | -4y-6=-3y-8 | | 8x=6(x-1) | | 565.2=1/3.22/7.6.6.h | | 8x^2+44x+60= | | 5x+4=46-2x | | 7+3=-5(3x-2) | | 7-2h=15-5h | | 45/w=5 | | 6x+100=10x-8 | | 1/4(11-8)=3/4 | | -8(2t+9)=-72 | | -8(2t+9)=-72t | | -5(f-67)+74=-1 | | 3m+4=7-3m |

Equations solver categories